3D‐printed polymer nanocomposites with carbon quantum dots for enhanced properties and in situ monitoring of cardiovascular stents. (9th December 2021) - Mahmud, Zaheri; Nasrin, Aklima; Hassan, Mahbub; Gomes, Vincent G.
Abstract: Nanocomposites are promising for manufacturing small diameter vascular biodegradable polymer‐based stents (BDPSs) to obviate frequent ordeals of in‐stent restenosis and stent thrombosis by providing appropriate support for vasculature as well as tissue regeneration. Freeform (without any support), vascular‐scale, small diameter (2 mm) tubular nanocomposites were fabricated using 3D printing based on fused filament fabrication (FFF). The nanocomposites were constructed using bioresorbable polylactic acid (PLA) and carbon quantum dots (CQDs). The3D‐printing process of the PLA‐CQD nanocomposites was optimized to deliver improved structural integrity as well as mechanical and biological properties for cardiovascular systems. The PLA‐CQD composites demonstrated excellent processability, hydrophilicity, tensile strength, compressive strength, radial stability, and cell proliferation relative to pure PLA. The results show that the addition of CQDs enhances stent properties significantly, such as, composite hydrophilicity by about 25%, tensile strength by 24%, compressive strength by 66%, and cell proliferation by 50% compared to PLA alone. The results show that the combination of 3D printing with PLA‐CQD nanocomposites could be a viable method to produce bioresorbable nanocomposites for cardiovasculatures with noninvasive imaging for monitoring composite condition and cell growth.